Advances in the insect industry within a circular bioeconomy context: a research agenda - Manal Hamam; Mario D’Amico; Giuseppe Di Vita (Environmental Sciences Europe, 2024)
Abstract The agri-food industry is increasingly recognizing the environmental impact of the over-exploitation of natural resources and waste production, which has prompted a search for sustainable alternatives based on circular bioeconomy principles. Insects can efficiently transform food substrates into reusable biomass, thus making them valuable contributors to a circular bioeconomy system. However, the relationship between the circular bioeconomy and the insect industry has so far appeared relatively unexplored in the existing research. To address this gap, a meta-synthesis has been conducted through a systematic literature review. By identifying the state of the art and assessing the role of insects in the transition of closed-loop systems, the aim of this research has been to shed light on the opportunities and challenges of integrating insects in circular bioeconomy strategies. The research revealed three main topics: (1) waste management by insects, i.e., the use of insects as a tool for waste management and with which to create high-value substrates; (2) insect-based feeds, namely the use of insects as alternative food sources in farming systems; (3) insect-based food acceptance by consumers. The results underscore the significant potential of this market within the circular bioeconomy context, highlighting the obstacles that need to be addressed and future strategies that could be adopted.